Transmission line compensation for power system stability improvement: article / Muhamad Qamarul Hafiz Abdullah - Abdullah, Muhamad Qamarul Hafiz (Universiti Teknologi MARA (UiTM), 2009)
Modem power systems which are rapidly growing, required constant attention to monitor their performance. Attention is also required to ensure that the voltage stability margin of the power system is above the desired level .This paper described the transmission line compensation to improve the system stability. In order to achieve the objective, three methods of line compensation were implemented, series capacitor, shunt capacitor and shunt reactor to improve the system stability by looking at the voltage regulation. The system stability is then compared with the Voltage Stability Index (L).This is done for three different transmission lines. The proposed methods were applied to 30 bus IEEE systems to show its feasibility and capability. All simulations were done using MATLAB version 7.5.